Aplikasi Monitoring Santri Berbasis Android Di Pesantren Mamba’ul Ma’arif Denanyar Jombang - Angga Lisdiyanto; Winarti; Agus Setia Budi; Arief Saputro; Syahri Mu’min; Rizky Aditya Nugroho (CV. ITTC INDONESIA, 2024)
This final project aims to address the challenges of monitoring students' development in Islamic boarding schools by leveraging technological advancements. The background of the problem highlights the insufficient supervision by parents over their children in boarding schools due to busy schedules and limited information received. The proposed application provides a solution by delivering real-time information on students' progress to parents, enabling them to monitor their children's grades and attendance remotely. The goal is to establish improved communication patterns between the boarding school and parents, as a step towards advancing education in Indonesia. Through research and testing, the Monitoring Activities of Students Application in High School-Level Education at Mamba’ul Maarif Islamic Boarding School in Denanyar Jombang has proven to be efficient and capable of providing detailed student data. The conclusion of this research indicates that the application has the potential to assist parents in better understanding their children's development during their stay at the boarding school